Fear of Loneliness: Development and Validation of a Brief Scale - Ventura-León, José; Sánchez-Villena, Andy Rick; Caycho-Rodríguez, Tomás; Barboza-Palomino, Miguel; Rubio, Andrés (Frontiers in Psychology, 2020)
This research aims to develop and validate The Brief Scale of Fear of Loneliness (BSFL). Participants were 1385 youth and adults, 347 from a pilot sample and 1038 from the final version, whose ages were in the range of 18 to 40 years. Two instruments, the Rosenberg Self-Esteem Scale and the De Jong Gierveld Loneliness Scale, in their Peruvian versions, were used to support the relationship with other variables. Results show that the BSFL should be interpreted as a one-dimensional measure, the same ones that were examined at the exploratory level and verified at the confirmatory moment (RMSEA < .08, CFI > .95), the reliability is considered good (ω > .88). In addition, the quality of the item content was reviewed by six expert judges for relevance and validity, with Aiken’s V being greater than .70. It is concluded that the BSFL is a valid and precise short instrument that can be used in future research studies.